The "Milliy Turkiston" Magazine as an Source of Valuable Information - Darmonova, Mashhuraxon (International Journal on Integrated Education, 2023)
Political and cultural organizations were created by our compatriots who remained abroad because of the repressive policies of the Soviet regime. These organizations carried out the struggle for national liberation and the reduction of the influence of Soviet power in Turkestan through the press and radio. The article talks about the magazine "Milliy Turkiston", a publication of the Turkestan Committee of National Unity.